2020
DOI: 10.3390/s20123476
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Group-IV Heisenberg-Limited Sagnac Interferometric Gyroscope at Room Temperature

Abstract: A room-temperature strip-guided “manufacturable” Silicon-on-Insulator (SOI)/GeSn integrated-photonics quantum-gyroscope chip operating at 1550 nm is proposed and analysed. We demonstrate how the entangled photons generated in Si Spontaneous Four Wave Mixing (SFWM) can be used to improve the resolution of a Sagnac interferometric gyroscope. We propose different integrated architectures based on degenerate and non-degenerate SFWM. The chip comprises several beam splitters, two SFWM entangled photon sources, a pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Based on this idea, many schemes of quantum gyroscopes have been proposed. It was found that the entanglement in N00N states [29,30], continuous-variable squeezing [31][32][33], and optical nonlinearity [34] can enhance the sensitivity of optical gyroscopes beyond the SNL. A quantumenhanced sensitivity can also be achieved in matter-wave gyroscopes [35][36][37][38] by using spin squeezing [39][40][41] or entanglement.…”
mentioning
confidence: 99%
“…Based on this idea, many schemes of quantum gyroscopes have been proposed. It was found that the entanglement in N00N states [29,30], continuous-variable squeezing [31][32][33], and optical nonlinearity [34] can enhance the sensitivity of optical gyroscopes beyond the SNL. A quantumenhanced sensitivity can also be achieved in matter-wave gyroscopes [35][36][37][38] by using spin squeezing [39][40][41] or entanglement.…”
mentioning
confidence: 99%